An analysis of protection system reliability in the distribution network at PT PLN Rayon West Binjai - Josua Delpiero Sinaga; Solly Aryza; Zuraidah Tharo (Sean Institute, 2024)
Continuity in the distribution of electrical energy is the main aspect in supporting all economic, social and development activities. The reliability of the distribution system has an important role in distributing electricity to customers. Disturbances that occur in the distribution system result in outages for customers. This paper describes system reliability which is influenced by system configuration, installed safety devices and the protection system. The reliability index is a benchmark indicator for viewing or describing the reliability of a distribution system expressed in terms of probability. In writing this final assignment, an analysis was carried out on the reliability of the protection system on the distribution network at PT PLN Rayon Binjai Barat by looking for the value or number of distribution system failure rates, the SAIDI Index (System Average Interruption Frequency Index) and the SAIFI index (System Average Interruption Frequency Index) as an indicator of the distribution system reliability index in obtaining the index value, the calculation is carried out with a customer orientation. In determining whether the distribution system is reliable or unreliable, PT PLN Rayon Binjai Barat has set a cumulative target index of 1031.778 for SAIDI and 10.0023 for SAIFI. The distribution system can be said to be reliable if the realized SAIDI and SAIFI values are below the predetermined targets